THE IMPACT OF ARTIFICIAL INTELLIGENCE ON SPECIALIZED LEARNING MOTIVATION IN HIGHER EDUCATION: A CONCEPTUAL PAPER - Muhamad Nasrullah Zamri; Muhammad Ridhwan Mat Zaki; Nur Zarifah Mohammad Nazri; Ami Afiza Mohammed Suhaimi; Nor Tasnim Syahera Rasak; Hanis Marhaini Masri; Muhammad Hafiz Suhaimi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores how Artificial Intelligence (AI) influences student motivation in specialized learning within higher education. As AI tools like intelligent tutoring systems, personalized feedback, and gamified platforms become more common, they offer new ways to support student engagement, autonomy, and learning interest. Using a literature review approach, the study examined research published between 2019 and 2025 from databases such as Scopus, Web of Science, Google Scholar, and Emerald Insight. The findings show that AI can improve motivation by personalizing learning, providing real-time support, and making learning more interactive. However, the study also highlights concerns about over-reliance on AI, fairness, and ethical use. A conceptual framework is proposed to help educators and researchers understand how AI can be used effectively and responsibly to support student motivation in field-specific academic settings.